Reflection of the migrant crisis on the security of the Republic of Serbia - Kovačević Nenad V.; Kovač Mitar P. (Војно дело, 2017)
The migrant crisis, the consequence of a deliberate plan or a set of circumstances, is in any case the event that undermines the richest confederation today - the European Union, and also all the countries that are on the migrant route. This paper analyzes the causes of the most massive contemporary 'migration', as well as its consequences for the countries of the European Union, as well as other transit countries. The Republic of Serbia has the large fluctuation of migrants. Therefore, the migrant crisis is considered through the prism of a threat to its national security. The paper also presents the tendencies of further development of the migrant crisis.